(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study evaluates the comparative financial performance of public and private sector banks in India, focusing on how variations in ownership structures, management practices, and risk profiles influence financial outcomes. The analysis is based on both secondary and primary data sources. Secondary data are drawn from the annual reports of selected banks and publications of the Reserve Bank of India over an extended period, ensuring a more comprehensive and reliable assessment. The study employs key financial ratios related to profitability, asset quality, capital adequacy, liquidity, and operational efficiency within the CAMEL framework to assess the overall strength and stability of both banking segments. To enhance analytical depth, the research incorporates structured evaluation techniques that support meaningful comparison and interpretation of results. In addition, primary data collected through a structured questionnaire (Google Forms) capture customer perceptions regarding service quality, digital banking services, and overall satisfaction. The integration of empirical findings with relevant theoretical perspectives strengthens the study’s contribution to understanding performance differentials across bank types in the evolving post-reform banking landscape.